The Development of The Telegram Bott As a Personalize Learning Model Project Based Learning Media in Kinematic Materials - Falah, Hebat Shidow; Jailani, Syarif Mahmud; Kurniawan, Wawan; Pujaningsih, Febri Berthalita; Dharma, Budi Eka (Science and Mathematics Education Journal, 2025)
Online learning poses challenges in teacher-student interaction, particularly in directing individualized attention to students. Effective learning media are critical to stimulating engagement and ensuring structured guidance. This study addresses the need for innovative tools to optimize project-based learning (PjBL) in physics, specifically for kinematic materials (quantities and units, uniformly changing straight motion, and free fall motion). This research aims to develop a personalized Telegram bot as a PjBL-compatible learning medium to enhance interaction and direction in online physics instruction. The study employs a Research and Development (R&D) framework guided by the design thinking model, comprising five stages: (1) empathize (understanding user needs), (2) define (problem identification), (3) ideate (solution brainstorming), (4) prototype (bot development), and (5) test (iterative evaluation). Testing involved three phases: blackbox testing (functionality), media expert validation (usability), and material expert validation (content relevance). The developed Telegram bot (accessible at https://t.me/learningphysicsbot) achieved a feasibility score of 92.94% from media experts (one physics education lecturer) and 95.00% from material experts (two physics education lecturers), both categorized as "very feasible." The bot successfully integrates PjBL principles, enabling structured, interactive, and self-directed learning for kinematic topics. This study demonstrates that a personalized Telegram bot is a highly feasible solution to overcome interaction barriers in online learning. It offers educators a practical tool to implement project-based methodologies effectively, fostering student engagement and autonomous learning. The findings highlight the potential of chatbot technology to transform digital classrooms into dynamic, student-centered environments.